EFEKTIVITAS AKUN TIKTOK @CNNIDONESIA SEBAGAI MEDIA BERITA DI KALANGAN MAHASISWA KOMUNIKASI PENYIARAN ISLAM FAKULTAS DAKWAH DAN KOMUNIKASI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Juliana Damayanti; Abdul Karim Batubara (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
This study aimed to examine the effectiveness of the TikTok account @cnnindonesia as a national news medium among students of the Islamic Broadcasting Communication (KPI) Program at the State Islamic University of North Sumatra. The research employed a quantitative survey method involving 100 respondents selected from a population of 323 students using the Slovin formula with an 8.3% margin of error. Data were collected through Likert-scale questionnaires and were analyzed using SPSS, including validity testing, reliability testing, and descriptive statistical analysis. The findings showed that all questionnaire items were valid (r-count > 0.196) and reliable (Cronbach’s Alpha = 0.867). The overall mean score for effectiveness was 4.02, which was categorized as good. The highest mean scores were found in content attractiveness and information needs (4.07), followed by information clarity (4.05) and credibility (3.96). The study concluded that the @cnnindonesia TikTok account was effective as a national news medium among students and reflected a shift in information consumption from conventional media toward social media, particularly TikTok.